Signature Pattern Recognition using Kohonen Network - Sari, Nadia Roosmalita; Sarwani, Mohammad Zoqi; Aulia, Yudha Alif; Mahmudy, Wayan Firdaus (Knowledge Engineering and Data Science, 2018)
A signature is a special form of handwriting that used for human identification process. The current identification process is extremely ineffective. People have to manually compare signatures with the previously stored data. This study proposed SOM Kohonen algorithm as the method of signature pattern recognition. This method has able to visualize high-dimensional data. The image processing method is used in this study in pre-processing data phase. The accuracy of SOM Kohonen was 70 %, indicated the method used was good enough for pattern recognition.